Left ventricle- and skeletal muscle-derived fibroblasts exhibit a differential inflammatory and metabolic responsiveness to interleukin-6 - Matz, Isabell; Pappritz, Kathleen; Springer, Jochen; Van Linthout, Sophie (Frontiers in Immunology, 2022)
Interleukin-6 (IL-6) is an important player in chronic inflammation associated with heart failure and tumor-induced cachexia. Fibroblasts are salient mediators of both inflammation and fibrosis. Whereas the general outcome of IL-6 on the heart’s function and muscle wasting has been intensively studied, the influence of IL-6 on fibroblasts of the heart and skeletal muscle (SM) has not been analyzed so far. We illustrate that SM-fibroblasts exhibit higher basal mRNA expression of α-SMA, extracellular matrix molecules (collagen1a1/3a1/5a1), and chemokines (CCL2, CCL7, CX3CL1) compared to left ventricle (LV)-fibroblasts. IL-6 drives the transdifferentiation of fibroblasts into myofibroblasts as indicated by an increase in α-SMA expression and upregulates NLRP3 inflammasome activity in both LV- and SM-fibroblasts. IL-6 increases the release of CCL7 to CX3CL1 in the supernatant of SM-fibroblasts associated with the attraction of more pro(Ly6Chi)- versus anti(Ly6Clo)-inflammatory monocytes compared to unstimulated fibroblasts. IL-6-stimulated LV-fibroblasts attract less Ly6Chi to Ly6Clo monocytes compared to IL-6-stimulated SM-fibroblasts. In addition, SM-fibroblasts have a higher mitochondrial energy turnover and lower glycolytic activity versus LV-fibroblasts under basal and IL-6 conditions. In conclusion, IL-6 modulates the inflammatory and metabolic phenotype of LV- and SM-originated fibroblasts.